PENGARUH KNOWLEDGE MANAGEMENT, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR TELEVISI REPUBLIK INDONESIA ( TVRI ) KENDARI - Muhammad Ing Nauffal Daharing; Samdin Samdin; Muhammad Masri; Abdul Razak Yusuf (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to examine and explain the effect of knowledge management, organizational culture and organizational commitment on employee performance at the Indonesian Television Office (TVRI) Kendari either simultaneously or partially.The approach of this research is survey with explonatory research design. Data was collected using an instrument in the form of a questionnaire. The population of this study were all permanent employees at the TVRI Kendari Office with a sample of 54 people. The analytical tool used for the hypothesis is multiple linear regression analysis.The results showed that the variables of knowledge management, organizational culture and organizational commitment simultaneously and partially had a positive and significant effect on employee performance at the TVRI Kendari office. This fact shows that the better knowledge management, organizational culture and organizational commitment will improve employee performance. Respondents perceive that employee performance is good or in other words, employees generally have high quantity and quality, optimal use of time and cost savings, as well as independence and good cooperation.